Német gazdasági előretörés a Südostraumban az 1930-40-es években - Szávai, Ferenc (Közép-Európai Közlemények, 2015)
Germany viewed the South-East European region as a potential economic zone of influence, but after the First World War it lost its function in the region. During the thirties Germany came out on top of the rivalry of the great powers and gained significant economic influence through the purchase of the agricultural stock holdings of the South-East European countries, but the support of the German minorities living in these countries was also a means to increase its influence. They were present at corporate and business level, and also in the organizations of Central-European countries. The German economic policy deliberately integrated the small countries’ market into their own large market space and the small countries had no other choice but to accept this.